Comparative assessment of the Sikun 2000 sequencing platform for whole genome sequencing - Keya Cai; Sibin Li; Meng Pan; Hui Lu; Liang Wang; Shengquan Fang; Lingzhi Gou; Jiang Tang; Yan Kong; Li Zhao; Yongyong Ren (Scientific Reports)
Abstract DNA sequencing technology has significantly advanced over the past five decades, particularly with the introduction of next-generation sequencing (NGS) platforms like Illumina’s NovaSeq. In October 2023, Sikun introduced the Sikun 2000, a desktop NGS platform designed for rapid, cost-effective sequencing with up to 200 Gb of data per run. This study is the first to evaluate the performance of the Sikun 2000 in whole genome sequencing (WGS) and compares it with the Illumina NovaSeq 6000 and NovaSeq X platforms using five well-characterized human Genomes in a Bottle dataset. Results show that the Sikun 2000 performs competitively in variant detection, particularly excelling in single nucleotide variant accuracy. It also demonstrated a higher sequencing depth and lower proportion of low-quality reads than the NovaSeq platforms. However, its performance in insertion-deletion (Indel) detection was slightly lower than that of NovaSeq platforms. Overall, the Sikun 2000 is a qualified sequencing platform for WGS, and further evaluation in clinical and research applications is required as data continues to accumulate.